Performing Resistance/Negotiating Sovereignty: Indigenous Women's Perofrmance Art in Canada - Taunton, Carla Jane (Queen's University, 2011)
Performing Resistance/ Negotiating Sovereignty: Indigenous Women’s Performance Art In Canada investigates the contemporary production of Indigenous performance and video art in Canada in terms of cultural continuance, survivance and resistance. Drawing on critical Indigenous methodology, which foregrounds the necessity of privileging multiple Indigenous systems of knowledge, it explores these themes through the lenses of storytelling, decolonization, activism, and agency. With specific reference to performances by Rebecca Belmore, Lori Blondeau, Cheryl L'Hirondelle, Skeena Reece and Dana Claxton, as well as others, it argues that Indigenous performance art should be understood in terms of i) its enduring relationship to activism and resistance ii) its ongoing use as a tool for interventions in colonially entrenched spaces, and iii) its longstanding role in maintaining self-determination and cultural sovereignty.
Accepted: 2011-09-30T21:33:54Z
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé